Role of whey protein in post-workout recovery - Gu, C. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Evidence indicates that whey protein supplementation may accelerate tissue repair and be useful for exercise-induced muscle injury (EIMD) by accelerating recovery and elevating protein synthesis and blood amino acids. However, the potential role of whey protein after EIMD in humans is inconsistent. Objective: Find the effective role of whey protein in post-exercise recovery from EIMD. Methods: Scopus, Medline, and Google scholar, were systematically searched until March 2022. To assess the risk of bias, the Cochrane collaboration tool was applied. Weighted mean differences (WMD), 95% confidence intervals (CI), and random effect models to calculate the total effect. Results: The result of the review indicated that the decreasing impact of whey protein intake is significant on creatine kinase (CK) [WMD = -19.11 IU.L-1, CI: -36.200, -2.036; P = 0.028]. The effect of whey protein supplementation on lactate dehydrogenase (LDH) concentration indicated that the impact of whey protein on changing LDH levels is significant. In addition, subgroup analysis showed significant decreases in CK and LDH based on post-exercise follow-up times, whey protein dosage, test duration, supplementation time, exercise types, and training status. Conclusion: The results showed the efficacy of whey protein in decreasing CK and LDH levels among adults in general and in subgroup analysis. Therefore, whey protein could have an effective role in the post-exercise recovery of EIMD.